Nanosuspension as Promising and Potential Drug Delivery: A Review: Pharmaceutical Science-Pharmaceutics for enhanced drug delivery - Haranath Chinthaginjala; Hindustan Abdul Ahad; Pushpalatha Gutty Reddy; Kalpana Kodi; Sai Priyanka Manchikanti; Devika Pasam (International Journal of Life Science and Pharma Research, 2022)
In the last decade, nanosuspensions have gained considerable interest as a method for formulating poorly soluble drugs. Because of their cost-effectiveness and technological simplicity compared to liposomes and other colloidal drug carriers, nanoscale systems have recently received a lot of attention as a way of solving problems of solubility. Nanosuspensions are biphasic systems comprising of pure drug particles dispersed in an aqueous vehicle, stabilized by surface active agents. Fabrication of nanosuspension is simple and more advantageous than other approaches. Nanosuspension is a very finely single solid drug particle in an aqueous vessel, stabilized by surfactants for either oral or topical use or for parenteral and pulmonary administration, it can also be used for targeted drug delivery when incorporated in the ocular inserts and mucoadhesive hydrogels, with reduced particle size resulting in increased dissolution rate. This article covers the preparation of nanosuspension by bottom up technology, top down technology, melt emulsification, emulsification- solvent evaporation and supercritical fluid with their advantages and disadvantages, aspects of structure, classification and their drug delivery applications. Nanosuspension can be processed for the drugs which are of hydrophobic in nature quite easily employing stability enhancers, solvents that are of organic and additional ingredients including buffering agents, salts, PEG, osmotic agents and anti-freeze compounds.